System Intersections-Concepts, Simulation Studies, and Potential Applications - Zhang W. (2017)
© ASCE. When an intersection becomes congested, the traditional way of increasing capacity is to widen the road and add lanes. This approach introduces more conflicts at the intersection and its effect is limited. In recent years, the concept of alternative intersection design is gaining recognition among practitioners and more implementations. This method increases capacity by adding auxiliary intersections that re-route certain traffic movements. By doing so, it reduces the number of conflicts at the main intersection and enables more simultaneous traffic movements, often without the need of widening the roadway. However, it does force drivers on certain approaches to travel extra distance to achieve better intersection level of service. This paper introduces a new concept called system intersection, in which a portion of the traffic demand at a congested intersection is dynamically diverted to a nearby intersection that has spare capacity, and traffic diversion is needed only during the peak period.